MEMBANGUN ORGANISASI/PERUSAHAAN MELALUI “STAKEHOLDER RELATIONS” - Melita, Yerah (Jurnal Insani, 2017)
Goals to be achieved organization/ company is built, maintained and the creation of a good or harmonious relationship between the organization with the public. Public in public relations has two parts, namely the internal public and the external public. Either the internal public or the external public should receive the same concern and care from the organization/ company.Internal public and external public are often called stakeholders. Stakeholders are the parties that have a big share in the growth and development of the organization/ company. Without stakeholder relations, organizations will not exist and will never exist. Therefore, the organization/ company assesses the importance and need to care about the existence of its stakeholders.